2018
DOI: 10.1093/ajcn/nqx008
|View full text |Cite
|
Sign up to set email alerts
|

Intake of free sugars and micronutrient dilution in Australian adults

Abstract: Background:The negative health effect of excessive intake of free sugars has been gaining increasing public awareness.Objective: This secondary analysis aimed to evaluate the impact of free-sugar intake on micronutrient dilution, and estimate a threshold level of free-sugar intake at which a decrease in micronutrient intake becomes evident, based on data from the Australian Health Survey 2011-2012. Design: Dietary data from adult respondents (weighted n = 6150) who had completed two 24-h recalls were analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…Little is known about the potential for micronutrient dilution at higher added sugar intakes in the diet of the U.S. adult population. One study based on the National Health and Nutrition Examination Survey (NHANES) 2003-2006 has shown an inverse relationship with added sugars intake for some micronutrients [14]; however, there is a paucity of other evidence, most of which is from populations outside of North America [15][16][17] and/or on other measures of sugars intake, such as sugar-sweetened beverages [18] and free sugars [19]. It is also reasonable to speculate that micronutrient dilution of the diet might not be as evident in adults compared with children because adults have a higher calorie intake and a generally more varied food intake than children.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the potential for micronutrient dilution at higher added sugar intakes in the diet of the U.S. adult population. One study based on the National Health and Nutrition Examination Survey (NHANES) 2003-2006 has shown an inverse relationship with added sugars intake for some micronutrients [14]; however, there is a paucity of other evidence, most of which is from populations outside of North America [15][16][17] and/or on other measures of sugars intake, such as sugar-sweetened beverages [18] and free sugars [19]. It is also reasonable to speculate that micronutrient dilution of the diet might not be as evident in adults compared with children because adults have a higher calorie intake and a generally more varied food intake than children.…”
Section: Introductionmentioning
confidence: 99%
“…from 5 E% to 25 E%) of sugar intake (IoM, 2005;Moshtaghian et al, 2016;Mok et al, 2018). In addition, the Panel considers that the way in which sugar intakes may be related to the micronutrient (and fibre) density of the diet and micronutrient (and fibre) intake largely depends on the particular foods in which sugars are present (e.g.…”
Section: Panel's Consideration Of the Comments Receivedmentioning
confidence: 99%
“…In the new release of the EFSA Comprehensive Food Consumption Database (published on 26 April 2018) 10 , data from national food consumption surveys which was available in FoodEx (4 levels) has been reclassified in FoodEx2 (7 levels, plus facets).…”
Section: Panel's Consideration Of the Comments Receivedmentioning
confidence: 99%
See 1 more Smart Citation
“…A vast body of modern research has concluded that while sugar is associated with several conditions, its role in their causation remains confounded, with the possible exception of dental caries. Of course, extreme high-sugar diets displace more nutritious foods and deplete essential micronutrients (7,8). When the city of Glasgow expanded from a small regional town to become the second city of the empire in the 19th century, there was no food provision service, and the population demand was met with a stereotypic imported diet of white bread, jam and sugary tea, which persisted through habit and regional poverty as ship-building declined, well into the 20th century.…”
mentioning
confidence: 99%